1996
DOI: 10.1097/00000542-199601000-00019
|View full text |Cite
|
Sign up to set email alerts
|

New Ultrathin-walled Endotracheal Tube with a Novel Laryngeal Seal Design

Abstract: The novel, no-pressure seal design of the new ETT is highly effective in preventing air leak and aspiration. It causes no significant tracheal injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 14 publications
0
25
0
2
Order By: Relevance
“…21 Gills have been shown to form an effective seal (> 40 cm H 2 O) with the glottis when incorporated into tracheal tube design. 22 We found that flexible lightwand-guided intubation with the PAX had a first attempt insertion success rate without adjusting maneuvers of 60%, a first attempt insertion success rate with adjusting maneuvers of 79% and an overall intubation success rate of 82%. This compares with a first attempt insertion success rate without adjusting maneuvers of 62%, a first attempt insertion success rate with adjusting maneuvers of 92% and overall intubation success rate of 100% for flexible lightwand-guided intubation with the intubating laryngeal mask airway.…”
Section: Me Et Th Ho Od Ds Smentioning
confidence: 76%
See 1 more Smart Citation
“…21 Gills have been shown to form an effective seal (> 40 cm H 2 O) with the glottis when incorporated into tracheal tube design. 22 We found that flexible lightwand-guided intubation with the PAX had a first attempt insertion success rate without adjusting maneuvers of 60%, a first attempt insertion success rate with adjusting maneuvers of 79% and an overall intubation success rate of 82%. This compares with a first attempt insertion success rate without adjusting maneuvers of 62%, a first attempt insertion success rate with adjusting maneuvers of 92% and overall intubation success rate of 100% for flexible lightwand-guided intubation with the intubating laryngeal mask airway.…”
Section: Me Et Th Ho Od Ds Smentioning
confidence: 76%
“…10 The efficacy of seal (25-35 cm H 2 O) was higher than the cuffed oropharyngeal airway (16)(17)(18)(19)(20)(21)(22) and Laryngeal Tube Airway™ (30 cm H 2 O). 9 We found that inflating the cuff from 30 to 60 mL improved the seal from 26 to 35 cm H 2 O.…”
Section: Me Et Th Ho Od Ds Smentioning
confidence: 98%
“…This tube appears to prevent the passage of oropharyngeal fluid into the lungs in sheep, using methylene blue placed in the oropharynx as a marker [12].…”
Section: Discussionmentioning
confidence: 99%
“…This dual-cuff technology allows the rubber outer cuff to adhere firmly to the tracheal wall while avoiding compression of the mucosa. A fourth option is to replace the standard cuff with several ring-shaped disks ("gills") made of thin polyurethane film (0.025-0.075 mm thick) [16]. This cuffless endotracheal tube conforms to the opening of the glottis and prevents leakage of secretions in intubated sheep.…”
mentioning
confidence: 99%